Evaluation of Treatment Response in Chronic Hepatitis C Patients Receiving Sofosbuvir/Velpatasvir/Voxilaprevir: A Multicenter Real-World Experience from Türkiye - Umut Devrim Binay; Faruk Karakeçili; Bilgehan Aygen; Ayşin Kılınç Toker; İlhami Çelik; Neşe Demirtürk; Tuğçe Şimşek Bozok; Leyla Dursun; Fethiye Akgül; Güle Çınar; Özgür Günal; Ali Asan; et al. (Viruses, 2025)
The combination of sofosbuvir/velpatasvir/voxilaprevir (SOF/VEL/VOX) is recommended as a salvage therapy for treatment-experienced chronic hepatitis C (CHC) patients. However, it is used in our country for treatment-naïve and treatment-experienced patients. This study aims to present real-world data from Türkiye on CHC patients treated with SOF/VEL/VOX. The present study was conducted by the Viral Hepatitis Study Group of the Turkish Society of Clinical Microbiology and Infectious Diseases (KLİMİK). It was a multicenter, retrospective, observational study. The data were collected from patients receiving SOF/VEL/VOX therapy at 12 medical centers in Türkiye between 1 June 2022 and 31 December 2024. The patients had received the treatment for 8 to 12 weeks. Of the 139 patients enrolled, 63.3% (n = 88) were male, with a mean age of 54.4 years. Most patients were non-cirrhotic (94.2%, n = 131) and treatment-naïve (92%, n = 128); 49.6% (n = 69) were infected with genotype 1b. Early virologic response (EVR) could be assessed in 126 patients, with an EVR rate of 82.5% (n = 104). End-of-treatment data were available for 113 patients, all achieving an end-of-treatment response. Among the 80 patients for whom week-12 post-treatment data were available, 97.5% sustained virologic response at week 12 (SVR12). Significant improvements were observed in AST, ALT, and platelet levels, along with reductions in APRI and FIB-4 scores (p = 0.001).” No serious adverse events leading to treatment discontinuation were reported. Mild adverse events included pruritus (2.1%, n = 3), fatigue (2.1%, n = 3), and nausea (1.4%, n = 2). The SOF/VEL/VOX combination is a highly effective and well-tolerated treatment option in treatment-naïve CHC patients, achieving an SVR12 rate of 97.5%.